Errors in The Acquisition of Various Grammar Items by Vietnamese Students at Elementary Level: 初级水平越南学生习得各项语法项目的偏误情况 - Dang Thu Lan (Published by Confucius Institute UNS, 2023)
This article uses test papers from students at Ho Chi Minh University of Banking (HUB) in Vietnam as the interlanguage corpus. According to the